2021
DOI: 10.1021/acs.jcim.1c00851
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Virtual Screening and Validation of a SARS-CoV-2 Main Protease Noncovalent Inhibitor

Abstract: Despite the recent availability of vaccines against the acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the search for inhibitory therapeutic agents has assumed importance especially in the context of emerging new viral variants. In this paper, we describe the discovery of a novel noncovalent smallmolecule inhibitor, MCULE-5948770040, that binds to and inhibits the SARS-Cov-2 main protease (M pro ) by employing a scalable high-throughput virtual screening (HTVS) framework and a targeted compound library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 63 publications
3
72
0
Order By: Relevance
“…Regarding neoechinulin A ( 1 ) and echinulin ( 2 ), they both achieved stable binding inside the M pro active site with average RMSDs of 2.16 Å and 2.21 Å, respectively. The dynamics of these two related structures (i.e., compounds 1 and 2 ) over the course of the simulation were also convergent to that of the reported co-crystallized ligand (RMSD ~2 Å) [ 25 ] ( Figure 4 B).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Regarding neoechinulin A ( 1 ) and echinulin ( 2 ), they both achieved stable binding inside the M pro active site with average RMSDs of 2.16 Å and 2.21 Å, respectively. The dynamics of these two related structures (i.e., compounds 1 and 2 ) over the course of the simulation were also convergent to that of the reported co-crystallized ligand (RMSD ~2 Å) [ 25 ] ( Figure 4 B).…”
Section: Resultssupporting
confidence: 66%
“…As shown in Figure 7 , the unbinding of eurocristatine ( 3 ) (i.e., the inactive compound) was achieved by a force not higher than ~108 pN, while active compounds neoechinulin A ( 1 ) and echinulin ( 2 ) along with the co-crystalized inhibitor YD1 required an unbinding force ranging from 399 pN to 909 pN. The force profile plotted in Figure 7 clearly indicated that neoechinulin A ( 1 ) (IC 50 = 0.47 µM) has the highest binding stability inside the M pro active site (i.e., needed unbinding force ~909 pN), followed by the co-crystalized inhibitor YD1 ( K i = 2.9 µM) [ 25 ] (i.e., needed unbinding force ~685 pN) followed by echinulin ( 2 ) (IC 50 = 3.9 µM) (i.e., needed unbinding force ~399 pN). These differences in the unbinding forces between neoechinulin A ( 1 ), echinulin ( 2 ), and the co-crystalized inhibitor YD1 may be attributed to the degree of ligand–protein H-bonds’ stability during the unbinding process in addition to the degree of hydrophobic interactions with hydrophobic residues inside the enzyme active site, particularly with HIS-41, where neoechinulin A ( 1 ) was able to establish a significant stable hydrophobic interaction with this hydrophobic residue ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…For example, several research groups have focused their attention on structure-based drug design of noncovalent M pro inhibitors starting from the anti-epileptic drug perampanel 28 , 29 , or from ML188 and ML300 previously designed to inhibit SARS-CoV-1 M pro 30 33 . We have recently performed a structure-activity relationship study 34 on a noncovalent compound newly discovered by high-throughput virtual screening 35 . Others have designed and evaluated a series of peptidomimetic reversible or irreversible covalent inhibitors 36 38 , or nonpeptidic small molecules with a novel chemical scaffold 39 .…”
Section: Introductionmentioning
confidence: 99%
“…21,284,498 compounds scored lower than −35 kcal/mol and the poses of top scoring 5,004,192 compounds were extracted. 214,580 compounds formed favorable interactions with key residues such as His163, Glu166 and the P2 subpocket, 181,866 of which obtained ECFP4-based TC coefficients of less than 0.35 to the 1,716 known SARS-CoV and SARS-CoV-2 MPro inhibitors reported in the literature 24, 8, 9, 11, 12, 14, 17, 20, 26, 28, 5975 . Finally, roughly 9,000 top-ranking compounds were visually inspected, and 167 molecules were ordered from Enamine Ltd., 146 of which (87.4%) were successfully synthesized.…”
Section: Methodsmentioning
confidence: 99%